Analisis Literasi Keuangan, Fintech dan Gaya Hidup terhadap Pengelolaan Keuangan Milenial dengan Moderasi Jenis Kelamin - Rahayu, Nila; Agung Arista Pradnyani, I Gusti; Anwar, Adrianda; Bagas Muhammad Bagus Putra Sucipto, Raden (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The development of digitalization and globalization has driven the increasing use of digital financial services among the millennial generation. However, low financial literacy and a tendency towards a consumptive lifestyle remain issues in personal financial management. This study aims to examine the influence of financial literacy, financial technology, and lifestyle on the financial management of the millennial generation, with gender as a moderating variable. Sampling was conducted purposively to select 100 millennial respondents in Mataram City, using a quantitative associative research design. A five-point Likert scale questionnaire was used for data collection, and SPSS version 26 software was used to analyze the results using multiple linear regression and Moderated Regression Analysis (MRA). Based on the results of the study, financial literacy and the use of financial technology significantly improve the financial management of the millennial generation, but lifestyle has not been shown to have a significant impact. Furthermore, the relationship between financial management, fintech, lifestyle, and financial literacy is not influenced by gender. These results underscore the urgency of improving financial literacy and responsibly utilizing financial technology to support wiser and more sustainable financial management, particularly among the millennial generation